Design and evaluation of learning strategies for a group of radiographers in radiostereometric analysis (RSA). Issue 4 (November 2017) - Muharemovic, O.; Troelsen, A.; Thomsen, M.G.; Kallemose, T.; Gosvig, K.K.
Abstract: Introduction: The purpose of this study was to design and evaluate a radiostereometric analysis (RSA) program aimed at radiographers in order to increase their cognitive and practical skills, thereby increasing image quality and minimizing exposure repetition. Methods and materials: Twenty radiographers were randomized into two identically sized study groups. Training consisted of a theoretical and practical workshop using a phantom. Tests were performed to compare the effect of training to nontraining, and the effect of time duration on the maintenance of RSA skills. The effect of training was measured by a written test and three defined parameters influencing image quality. Results: Group A reduced significantly (p < 0.001) by 31.3 mm (21–31%) the distance between the centrum of the prosthesis (CP) and the centrum of the calibration field (CCF) and increased the number of beads (NB) visible by 3.6 (out of 18). A further significant reduction of 5.1 mm (p = 0.023), 1.0 bead more (p < 0.001) and a 2.1 (p = 0.022) point better rotation of the prosthesis (RP) was registered two months later. Group B was tested twice without training and no significant improvement was registered. One month after training group B had experienced overall significant improvement on a par with group A. Conclusion: It is realistic to implement an RSA X-ray training program where radiographers significantly improve their theoretical and practical skills in centering the CP closer to the CCF, NB and RP. A duration of up to two months after training does not influence the quality of participants' performance. Highlights: In vitro organized training program improved radiographers' RSA imaging skills. After training all radiographers improved their results in the written test. After training radiographers improved their skills in all three measured parameters. RSA imaging skills improvement contributed to radiation dose savings. The pauses between the tests did not affect the radiographers' performance.